2018
DOI: 10.1088/1361-6463/aaaedb
|View full text |Cite
|
Sign up to set email alerts
|

In situ Kerr and harmonic measurement in determining current-induced effective fields in MgO/CoFeB/Ta

Abstract: A combination of the harmonic measurement and in situ Kerr imaging was used to experimentally determine the spin–orbit (SO) effective fields in a MgO/CoFeB/Ta structure. Here, we evaluate the SO effective fields through an analytical energy approach by transforming the anomalous Hall effect and planar Hall effect (PHE) voltage into a field dependency while imaging the magnetisation behaviour by differential Kerr microscopy. The analytical fitting to the measurement data indicates the significant coexistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…At larger t Tb , the shunting of current in Pt greatly decreases; thus, this increases the contributing SHE from the Co/Tb interface. Therefore, [2,25,26], the reference sample gives rise to θ eff SH,Ta ≈ −0.11, which is within a reasonable range of the spin Hall angle reported for Ta [2,27]. Similarly, the spin Hall angle of Tb, θ eff SH,Tb can subsequently be derived from the ξ eff DL such that its value ranges from −0.18 ≤ θ eff SH,Tb ≤ −0.48 for 5 ≤ t Tb ≤ 9 nm.…”
Section: A Enhanced Sot Fields In Rare-earth Element Tbsupporting
confidence: 82%
See 1 more Smart Citation
“…At larger t Tb , the shunting of current in Pt greatly decreases; thus, this increases the contributing SHE from the Co/Tb interface. Therefore, [2,25,26], the reference sample gives rise to θ eff SH,Ta ≈ −0.11, which is within a reasonable range of the spin Hall angle reported for Ta [2,27]. Similarly, the spin Hall angle of Tb, θ eff SH,Tb can subsequently be derived from the ξ eff DL such that its value ranges from −0.18 ≤ θ eff SH,Tb ≤ −0.48 for 5 ≤ t Tb ≤ 9 nm.…”
Section: A Enhanced Sot Fields In Rare-earth Element Tbsupporting
confidence: 82%
“…The relative efficiency of the DL torque is a commonly used figure of merit for spin Hall material that relates proportionally to the effective spin Hall angle, ξ eff DL ∝ θ eff SH . The ongoing studies of 5d-transition heavy-metal (HM)-ferromagnetic (FM) interfaces has revealed strong intrinsic [23,24] spin Hall effects in Pt (θ eff SH,Pt = +0.09) [2,25,26], β-Ta (θ eff SH,Ta = −0.12) [2,27], and β-W (θ eff SH,W = −0.30) [14]. We continue to pursue the search for alternate spin Hall materials from a class of elements that have been comparatively unexplored, the f -electron rare-earth (R) metals.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were carried out in the wires with stacks of Ta( t nm)/Co(2 nm)/Pt(5 nm), where t = 4, 6, 8 and 10 20 . The fabrication and patterning processes of the wires are described elsewhere 17,20–22 . The SOT fields are quantified as a function of the longitudinal fields in the sample of Ta(4 nm)/Co(2 nm)/Pt(5 nm) 20 .…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…The dependence of the two effective fields on the orientation of the magnetization has been studied, especially in materials with perpendicular magnetic anisotropy (PMA) 1117 . Reported SOT measurements on Ta/CoFeB/MgO structures have shown that the damping-like term H D changed the direction when the magnetization is reversed 12 .…”
Section: Introductionmentioning
confidence: 99%
“…SOT serves as an efficient alternative for reversal of the magnetisation in the FM layer 36,37,39,117,119,130 and driving of DWs 8,74,121,122,172,173 . The origin of the SOT is attributed to both the spin Hall effect 36,47,61,148,174 (SHE) in the NM layer and the interfacial Rashba effect 48,49,58 . Recently, the f-electron rare-earth (R) metals have drawn increasing attention because of their substantial SHE contribution due to their partially filled f-orbitals 146,149 .…”
Section: Introductionmentioning
confidence: 99%